MULTIFUNCTIONALITY OF RADIO RECEIVING DEVICES - Samandar Khikmatov Third-Year Student (Western European Studies, 2025)
The article presents radio receiving devices that are designed to receive radio signals and convert them to a form that allows the use of the useful information contained in them.
Keywords: received signal decoding; frequency filtering; received signal processing